(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores the beliefs of Bukhara artisans and their philosophical perspectives on life. It examines their religious and ethical values, attitudes toward labor, and approaches to social and spiritual life. The study highlights how moral and social views are shaped through life experiences and work, and their philosophical significance within society. The research demonstrates how the beliefs of Bukhara artisans contribute to personal spiritual development, social justice, and the formation of ethical norms.